The role of vitamin D in the endocrinology controlling calcium homeostasis - Fleet, James C. (Molecular and cellular endocrinology, 2017)
Vitamin D and its' metabolites are a crucial part of the endocrine system that controls whole body calcium homeostasis. The goal of this hormonal control is to regulate serum calcium levels so that they are maintained within a very narrow range. To achieve this goal, regulatory events occur in coordination at multiple tissues, e.g. the intestine, kidney, bone, and parathyroid gland. Production of the vitamin D endocrine hormone, 1,25 dihydroxyvitamin D (1,25(OH)2 D) is regulated by habitual dietary calcium intake and physiologic states like growth, aging, and the menopause. The molecular actions of 1,25(OH)2 D on calcium regulating target tissues are mediated predominantly by transcription controlled by the vitamin D receptor. A primary role for 1,25(OH)2 D during growth is to increase intestinal calcium absorption so that sufficient calcium is available for bone mineralization. However, vitamin D also has specific actions on kidney and bone. •Calcium homeostasis controls serum calcium levels within a narrow range.•The vitamin D endocrine system controls whole body calcium homeostasis.•Habitual dietary calcium intake and physiologic states control vitamin D metabolism.•The primary role of vitamin D is to regulate intestinal calcium absorption.•Vitamin D also regulates urinary calcium excretion and bone metabolism.